Four-component electrophilic difunctionalization of olefins using sulfonic acids, cyclic ethers, and NBS. Issue 42 (14th October 2015) - Sohail, Muhammad; Khan, Muhammad; Zhang, Yixin; Peng, Chang; Chen, Qin; Zhao, Zongbao K.
Graphical abstract: Abstract: A novel and highly regio- and diastereoselective four-component reaction involving an olefin, a cyclic ether, a halogen reagent, and a sulfonic acid has been developed to access alkoxyether derivatives. Moderate to excellent yields were obtained with a broad substrate scope without external catalyst. Several of these sulfonate ester derivatives showed strong anticancer activity against human lung adenocarcinoma cells.